2015
DOI: 10.1371/journal.pone.0141973
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-Analysis of Ilizarov Methods in the Treatment of Infected Nonunion of Tibia and Femur

Abstract: BackgroundInfected nonunion of tibia and femur are common in clinical practice, however, the treatment of these diseases has still been a challenge for orthopaedic surgeons. Ilizarov methods can eradicate infection, compensate bone defects and promote the bone union through progressive bone histogenesis. The objective of this systematic review was to review current available studies reporting on Ilizarov methods in the treatment of infected nonunion of tibia and femur, and to perform meta-analysis of bone and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
105
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(113 citation statements)
references
References 31 publications
5
105
2
1
Order By: Relevance
“…Furthermore, recurrence of infection is common, affecting 10% to 20% of patients [11][12][13][14]. A structured approach, with adequate debridement, excision of necrotic tissue, antimicrobial therapy and reconstruction of the bone and soft tissues, is of immense importance to eradicate infection and restore function [15][16][17]. To manage the resulting bone defects, distraction osteogenesis techniques such as Ilizarov acute shortening with bifocal relengthening (ASR) and bone transport (BT) have been shown to be effective treatment options to achieve union and infection clearance [1,12,15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recurrence of infection is common, affecting 10% to 20% of patients [11][12][13][14]. A structured approach, with adequate debridement, excision of necrotic tissue, antimicrobial therapy and reconstruction of the bone and soft tissues, is of immense importance to eradicate infection and restore function [15][16][17]. To manage the resulting bone defects, distraction osteogenesis techniques such as Ilizarov acute shortening with bifocal relengthening (ASR) and bone transport (BT) have been shown to be effective treatment options to achieve union and infection clearance [1,12,15,16,18].…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review and meta-analysis of Ilizarov methods in treatment of infected non-unions by Yin et al (4) revealed an average bone union rate of 97.26%. Among the 590 patients with infected non-union of tibia and femur who were included in the review, the poor rate in bone results and functional results was only 8% and 10% respectively which was similar to that obtained in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Also, it aids to create the repair of angulation, multiplanar stability, and rotation at the nonunion place (1,5). The current study reported the experience at a teaching hospital to manage femoral supracondylar fractures fixed by Ilizarov technique.…”
Section: Introductionmentioning
confidence: 97%
“…Femoral supracondylar fracture contains 4% -7% of all femoral fractures (1). These fractures usually occur in females over 50 years old due to injury in a fall when walking and osteopenia, and in younger patients (males 15 -50 years) due to road accidents and sports injuries (1)(2)(3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation